Provably secured and lightweight authenticated encryption protocol in machine-to-machine communication in industry 4.0 - Ashrif, Fatma Foad; Sundararajan, Elankovan A.; Hasan, Mohammad Kamrul; Ahmad, Rami; Hassan Abdalla Hashim, Aisha; Abu Talib, Azhar (Elsevier, 2024)
Industry 4.0 and the industrial Internet of Things (IIoT) aim to create a platform for data-driven decision-making through machine-to-machine (M2M) communication, often facilitated by the 6LoWPAN standard. However, as a resource-constrained device, 6LoWPAN raises security and privacy concerns for M2M communications, necessitating efficient and lightweight authentication and key establishment (AKE) protocols. Existing AKE protocols relying on asymmetric and symmetric cryptographic keys are susceptible to attacks and entail significant storage, communication, and computation overheads. This study examines a scheme called SLAP to uncover vulnerabilities and challenges in AKE-based M2M deployments in IIoT, including traceability, denial of service (DoS), perfect forward secrecy (PFS), and ephemeral secret leakage (ESL) attacks. Therefore, a privacy-preserving, secure, and lightweight authenticated encryption protocol called provably secure, lightweight, authenticated encryption (PSLAE) is proposed to address these issues. This approach includes hash operations, XOR operations, and authenticated encryption primitives for lightweight and secure mechanisms. It uses a one-time alias identity and fresh parameters to ensure privacy and protection against traceability and DoS, PFS, and ESL attacks. PSLAE undergoes rigorous informal and formal verification through SVO logic and Scyther, demonstrating resilience against the extended Canetti–Krawczyk and Dolev–Yao threat models. Moreover, it provides a lightweight, secure, efficient, and reduced storage, communication, and computation overhead compared with related works for AKE-based M2M in IIoT.